CONSTRUCTION OF RECOMBINANT LACTOBACILLUS CASEI EXPRESSING AEROMONAS VERONII OMPF PROTEIN GENE - S. A. Siddiqui; K. Yuanhuan; Z. Dongxing; C. Long; Shan Xiaofeng; Q. Aidong (Journal of Animal and Plant Sciences, 2019)
Aeromonas veronii infection is significant common worldwide exists in aquatic environment, closely related to haemorrhagic septicaemia, severe skin and muscles tissues ulcers with high mortality. Therefore an effective and safe technique to eradicate Aeromonas veronii infection is urgently required. In this study we built-up straightforward system to construct the live recombinant lactobacillus oral OmpF vaccine candidate against newly isolated A. veronii strain TH0426. One protein of interest OmpF (1038bp) was expressed in secreting prokaryotic shuttle expressing plasmid pPG612.1. We identified strong expressions of novel recombinant plasmid by using extraction of plasmid, digestion by enzymes, PCR, immunoblot and sequence analysis. The recombinant plasmid pPG612.1-OmpF was transformed onto the Lactobacillus casei CC16 by electroporation, and developed the recombinant strain on L.casei-pPG612/OmpF. The results show OmpF gene had successfully inserted onto the expression recombinant vectors and achieved recombinant Lactobacillus systems.
Keywords: Aeromonas veronii; OmpF; gene cloning; prokaryotic expression; recombinant Lactobacillus casei